Suara Perempuan dalam Lagu Paduan Suara Dialita - Saraswati, Dyah Paramita (UI Scholars Hub, 2022)
The women, who survived the 1965 tragedy and had been political prisoners because they were thought to have ties to the Indonesian Communist Party, had been silenced for a long time. Those female survivors then spoke through songs in the Dialita Choir. What they do is a form of women’s writing which is an attempt to include women in historical narratives. This study aims to analyze their act as a form of feminine writing that can be seen through the lyrics of a song sung by the Dialita Choir. The lyrics from the Dialita Choir are treated as text. The analysis in this study uses a feminist perspective with a critical discourse analysis approach. This study found that written songs became a coping mechanism for them while being arrested.